EDUKASI GIZI BERBASIS MEDIA SOSIAL MENINGKATKAN PENGETAHUAN DAN ASUPAN ENERGI- PROTEIN REMAJA PUTRI DENGAN KURANG ENERGI KRONIK (KEK) - Zaki, Ibnu; Sari, Hesti Permata (PERSATUAN AHLI GIZI INDONESIA, 2019)
Chronic Energy Deficiency (CED) is a condition of female adolescent experiencing a lack of energy and protein intakes for a long period. Nowadays social media is a popular media among adolescents. The study aims to determine the effectiveness of social media in improving nutrition knowledge, energy and protein intakes of CED?s adolescent girls in rural and urban areas. A quasi experimental research design with one group pre-test post-test was applied, subject was taken with a purposive technique. A total of 56 CED teenage girls from SMAN 1 Baturraden represented rural group and 54 CED teenage girls from SMAN 5 Purwokerto represented urban group were taken. Knowledge was measured using a knowledge questionnaire, data on energy and protein intakes were collected using 2x24 hour Food Recall. Statistical analysis used were dependent T-test, Wilcoxon, Independent T-test, and Mann-Whitney. The average change in nutritional knowledge scores was 2.71 in rural area, and 2.48 in urban area. Average changes in energy intake in rural area was 510.66 kcal, and urban area was 592.43 kcal. Average changes in protein intake in rural area was 24.78 g, and urban area was 20.78 g. There was a difference before and after nutrition education on nutrition knowledge, energy intake, protein intake in rural areas (p = 0.000) and urban areas (p = 0.000). There was no difference in increasing nutritional knowledge (p = 0.899), energy intake (p = 0.426), protein intake (p = 0.663) between rural and urban areas. There were differences in nutrition knowledge, energy and protein intakes, before and after social media-based nutrition education given in rural and urban areas. However, the amount of improvement in the score of nutritional knowledge and energy-protein intakes, did not differ between rural and urban areas.